Anti-ABCG2 monoclonal antibody in combination with paclitaxel nanoparticles against cancer stem-like cell activity in multiple myeloma. (January 2014) - Yang, Cuiping; Xiong, Fei; Wang, Jing; Dou, Jun; Chen, Junsong; Chen, Dengyu; Zhang, Yu; Luo, Shouhua; Gu, Ning
Aim: To investigate the effects of anti-ABCG2 monoclonal antibodies (mAbs) in combination with paclitaxel iron oxide nanoparticles (PTX-NPs) on CD138 - CD34 - multiple myeloma (MM) cancer stem cells (CSCs) in JJN3 cells.Materials & methods: PTX-NPs were prepared using the hydrophobic interaction of the polyoxypropylene chain and oleic acid on the surface of iron oxide NPs and were targeted to the ABCG2 transporter overexpressing MM CSCs with mAbs.Results: The data showed that MM CSCs have strong drug resistance and tumorigenicity compared with non-MM CSCs. PTX-NPs combined with mAbs led to a significant reduction in the tumor volume, a visible alleviation of lytic bone lesions and a markedly increased survival rate in contrast to using a single agent in MM CSCs when it was transplanted to nonobese diabetic/severe combined immunodeficiency mice.Conclusion: This study is the first to report on the anti-MM CSC activity by PTX-NPs as a single agent or used together with anti-ABCG2 mAbs to treat MM. These findings provide a rationale for future clinical trials. Original submitted 18 June 2012; Revised submitted 29 November 2012; Published online 27 March 2013